THE EFFECTIVENESS OF INFORMATION SERVICES IN PREVENTING STUDENT VERBAL AGGRESSION IN JUNIOR HIGH SCHOOL OF JAMBI - Hijriani, Hijriani; Rasimin, Rasimin; Zubaidah, Zubaidah (Jurusan Bimbingan dan Konseling, 2024)
The study is entitled Effectiveness of Information Services in Preventing Verbal Aggression of Students in the Junior High School of Jambi. The focus of this research is verbal aggression that hurts someone with words. The aim of this research is to reveal whether information services prevent verbal aggression in the students of the Junior High School of Jambi. This study uses the type of quantitative research with the experimental research method of a one group pretest-posttest. The population in this study is the whole of the students of the 7th grade at the Junior High School of Jambi. Sampling techniques using cluster random sampling and lottery techniques obtained from samples of class VII I consisting of 33 students. The instruments used in this research are the lifting. The techniques used are the presentation test and the T-test. The results of this study show that: (1) the presence of students' pretest results is at a moderate level, (2) there are students' posttest results after information services have changed, (3) there is the effectiveness of information services in preventing verbal aggression of students.